Laboratory anatomy of the human body - Butterworth, Bernard B., 1923-; Butterworth, Bernard B. ([Dubuque, Iowa] : Wm. C. Brown Publishers, 1992)
(NtOW^ HURAANGUJs
Includes index.
Keywords: human anatomy; laboratory manuals